Pollen eDNA metabarcoding from ice cores as a tool for reconstructing plant biodiversity dynamics. A case study from the largest and deepest southern Alps glacier: Adamello, Italy - Marchesini, A.; Girardi, M.; Cristofori, A.; Maggi, V.; Festi, D.; Wellstein, C.; Zerbe, S.; Oeggl, K.; Vernesi, C. (country:IE, 2018)
DNA obtained from environmental samples (eDNA) is an important source of biological information and eDNA metabarcoding is an emerging approach for reconstructing biodiversity changes through space and time. Past eDNA can be retrieved from many different sources such as ice cores, permafrost, terrestrial and lake sediments, caves, speleothems, etc. To this end, Alpine glaciers can be viewed as precious climate and biological archives, located in the proximity of areas that are facing dramatic land use and climatic changes since the last decades. Due to the good preservation of pollen DNA in the ice and the detailed stratigraphy, they offer a unique opportunity to test the potential of eDNA metabarcoding approach, specifically aimed at investigating plant biodiversity dynamics in adjacent and surrounding areas. Despite the obvious power of this emerging molecular approach, several caveats associated with the eDNA metabarcoding workflow need to be considered: false positives due to contaminations, false negatives resulting from primer biases, errors due to cross-contamination and chimaera sequences. Moreover primer choice, that affects taxonomic coverage and resolution, the need of complete reference databases, as well as difficult interpretation of results relative to the nature and spatial scale of eDNA represent other critical issues. We first present and discuss different eDNA metabarcoding approaches (e.g. PCR-based sequencing vs PCR-free sequence-capture enrichment), together with their main advantages, limitations and challenges. Second, we show the preliminary results from CALICE (CALibrating Biodiversity from Glacier ICE), a three-years research project aimed at estimating plant biodiversity changes through the last decades in the Adamello glacier catchment area. Adamello is the largest, 16.4 km2, and deepest, 270 m, Italian glacier whose catchment area, mainly lying in the Po valley in Northern Italy, is characterized by strong anthropogenic pressure. Our results, referring to a 10 m section extracted ...